The effect of wages and work experiences on the commitment of Hungarian employees - Kozák, Anita; Krajcsák, Zoltán (Business: Theory and Practice, 2018)
The purpose of this study is to find out whether there is a verifiable correlation between the individuals’ employee commitment dimensions (affective, continuance, normative, professional and deliberate) and the personal characteristics of these employees. Our research was carried out among the employees of 56 organizations based in Hungary. Organizations were selected by snowball method. A total of 1731 questionnaires were processed, besides descriptive statistical methods we have used variance analysis. We have found significant correlations between the ages of employees and the level of affective, continuance, normative and professional commitment as well, by age-grouping and wage-grouping too. The results show that the first communication mode also has a significant impact on these four commitment dimensions, and all of the commitment dimensions had a higher level among employees who was enquired by the organization (the direction of the first communication is from the organization to the employee).